PEMIKIRAN EKONOMI DARI LENIN, REVISIONIS, DAN KIRI BARU,SERTA RELEVANSINYA DI INDONESIA SAAT INI - Ris Yuwono Yudo Nugroho (MediaTrend, 2014)
The ideological struggle is necessary to looking for guidance of social life. fromthe historical development of thinking really teach, that Lenin had modified the idea ofMarx, while the revisionists want to make social change not through violent revolutions,and with the softer style of socialism, in Europe and America later expanded a new left.The discussion ofseveralaspects of these ideasits relevancein Indonesia today,aseffortsto take a positive valueof each idea. The value ofhistoricalresearch,aremayrecognize the businesswhich has been done previously,help determinethe strategies and other ideas,and may providesolutionand the seeking the truthaboutthe present.Lenin and Rosa view of the importance of of qualified human resourcesconsequences to guarantee the quality of life of workers.The chargesagainstwageeligible,health insurance, and work facilities, become a things that shouldbe fulfilled.The protection of women workers is also a concern.Analysis of the New LeftRevisonis and become part of an early warning system in the future crises.